Teori Penentuan Bagian Ahli Waris Ashabul Furudh Menurut Konsep Syajarotul Mirats - Raja Ritonga; Martua Nasution (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
Ashabul furudh is a group of heirs who have a certain part in Islamic inheritance. In the process of determining the inheritance share, the ashabul furudh group takes precedence over other inheritance groups. The practice of this determination will determine the share of each heir and describe the heirs who do not inherit. This study will describe the process of determining the part of ashabul furudh through the concept of syajarotul mirats. The method used in this research is a qualitative method with the type of library research. So that in collecting data, a many of books and journals were searched that were relevant to the research theme. Furthermore, the data were analyzed by content analysis. The results of the study concluded that the order of kinship in the concept of syajarotul mirats greatly influences the process of determining the share of heirs. Furthermore, the concept also describes that each heir has a relationship with other heirs. So that each heir will affect the other heirs. Therefore, the results of this study are expected to provide scientific treasures in the practice of dividing Islamic inheritance.